Brain Temperature Alters Contributions of Excitatory and Inhibitory Inputs to Evoked Field Potentials in the Rat Frontal Cortex - Gotoh, Mizuho; Nagasaka, Kazuaki; Nakata, Mariko; Takashima, Ichiro; Yamamoto, Shinya (Frontiers in Cellular Neuroscience, 2020)
Changes in brain temperature have been reported to affect various brain functions. However, little is known about the effects of temperature on neural activity at the network level, where multiple inputs are integrated. In this study, we recorded cortical evoked potentials while altering the local brain temperature in anesthetized rats. We delivered electrical stimulations to the midbrain dopamine area and measured the evoked potentials in the frontal cortex, the temperature of which was locally altered using a thermal control device. We focused on the maximum negative peaks, which was presumed to result mainly from polysynaptic responses, to examine the effect of local temperature on network activity. We showed that focal cortical cooling increased the amplitude of evoked potentials (negative correlation, > 17°C); further cooling decreased their amplitude. This relationship would be graphically represented as an inverted-U-shaped curve. Pharmacological blockade of GABAergic inhibitory inputs eliminated the negative correlation (> 17°C) and even showed a positive correlation when the concentration of GABAA receptor antagonist was sufficiently high. Blocking the glutamatergic excitatory inputs decreased the amplitude but did not cause such inversion. Our results suggest that the negative correlation between the amplitude of evoked potentials and the near physiological local temperature is caused by the alteration of the balance of contribution between excitatory and inhibitory inputs to the evoked potentials, possibly due to a higher temperature sensitivity of inhibitory inputs.